All's Faire in Middle School - Victoria Jamieson (Dial Books, 2017)
Eleven-year-old Imogene (Impy) has grown up with two parents working at the Renaissance Faire, and she's eager to begin her own training as a squire. First, though, she'll need to prove her bravery. Luckily Impy has just the quest in mind--she'll go to public school after a life of being homeschooled! But it's not easy to act like a noble knight-in-training in middle school. Impy falls in with a group of girls who seem really nice (until they don't) and starts to be embarrassed of her thrift shop apparel, her family's unusual lifestyle, and their small, messy apartment. Impy has always thought of herself as a heroic knight, but when she does something really mean in order to fit in, she begins to wonder whether she might be more of a dragon after all.
Keywords: Adventure -- Adventure